Sensitivitas Metode Pemeriksaan Mikroskopis Fluorokrom dan Ziehl-Neelsen untuk Deteksi Mycobacterium tuberculosis pada Sputum - BETTY SURYAWATI; LELI SAPTAWATI; ASTARI FEBYANE PUTRI; JATU APHRIDASARI (Smart Medical Journal, 2018)
Background: Detection of fast acid bacteria (FAB) using smear microscopy is used as a primary screening for tuberculosis diagnosis. Previous studies have shown that fluorochrome (Auroamine-rhodamine) staining showed better sensitivity compared to Ziehl-Neelsen (ZN) method in the detection of FAB in sputum. However this method has not been recommended for routine use including in Indonesia. This study aimed to evaluate the sensitivity and specificity of fluorochrome compared to ZN to detect FAB in patient’s sputum.Methods: This study analyzed 60 sputum samples from patients with tuberculosis and suspected pulmonary tuberculosis. Samples were obtained consecutively from microbiology laboratory Moewardi Hospital, Indonesia. Each sample was examined using ZN and fluorochrome staining and cultured in Lowenstein-Jensen (LJ) medium. Data were analyzed using sensitivity and spesificity tests.Results: ZN staining detected FAB in 12 samples (10%), while fluorochrome detected FAB in 17 samples (28%). The sensitivity and specificity of ZN staining were 70% and 90% while these for fluorochrome were 90% and 84%. Conclusions: The sensitivity of fluorochrome staining is better compared to ZN staining. This method can be recommended for early detection of tuberculosis.